2010
DOI: 10.1175/2010mwr3102.1
|View full text |Cite
|
Sign up to set email alerts
|

Filamentation Time Diagnosis of Thinning Troughs and Cutoff Lows

Abstract: This paper analyzes synoptic-scale trough-thinning processes using a filamentation time diagnostic. The filamentation time diagnostic is derived from the potential vorticity equation expressed in spherical coordinates in the horizontal plane and the isentropic coordinate in the vertical direction. The diagnostic is an accurate measure of stirring processes under the condition of ''slowly varying velocity gradients.'' Troughthinning processes are analyzed for one tropical example and two midlatitude examples. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…These rapid changes occur in such processes as breakdown of a quasilinear PV strip and separation of the TC and wave. In a recent study, Tsai et al (2010) derived a version of the Okubo-Weiss filamentation time for three-dimensional divergent flow constrained by material conservation of isentropic PV. Adapting their formulation and neglecting the effect of Earth's curvature (given the proximity to the equator), the filamentation time is written as…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…These rapid changes occur in such processes as breakdown of a quasilinear PV strip and separation of the TC and wave. In a recent study, Tsai et al (2010) derived a version of the Okubo-Weiss filamentation time for three-dimensional divergent flow constrained by material conservation of isentropic PV. Adapting their formulation and neglecting the effect of Earth's curvature (given the proximity to the equator), the filamentation time is written as…”
Section: Datamentioning
confidence: 99%
“…where d, S, and z refer to divergence, total deformation, and relative vorticity on an isentropic surface respectively. As noted in Tsai et al (2010), the formulation is defined only for strain-dominated regions, and small values of this diagnostic indicate rapid increase in PV gradient and potential for cutoff low formation. Tsai et al (2010) examined three cases of PV filamentation of upper-level troughs, including one in the tropics.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the piecewise PV inversion reveals further that the barotropic flow exerted a strong deformation on the upstream flank of the trough beginning on 8 October (quantified by a filamentation time‐scale as in Tsai et al , ; Riemer and Jones, 2013, not shown). It is thus plausible to assume that the high‐amplitude ridge upstream of the trough was instrumental for the trough's evolution into an elongated feature.…”
Section: Large‐scale Dynamics and Predictabilitymentioning
confidence: 67%
“…Conversely, in the "vorticity-dominated regions", the vorticity exceeds the deformation ( E 2 < 2 ), and the fluid is in an elliptical mode of motion that advects the vorticity smoothly. The Okubo-Weiss criterion has been used to explain some phenomena in atmosphere such as the trough thinning and filamentation in tropical cyclones (Rozoff et al 2006;Wang 2008;Tsai et al 2010). It indicates that different values of deformation and vorticity could construct different flow patterns (deformation dominated or vorticity dominated) which then endure different weather developments.…”
Section: Physical Meanings Of the Interactions Of Sv/sd And Sementioning
confidence: 99%